জাতীয়তাবাদ, সাম্প্রদায়িকতা ও জনগণের মুক্তি, ১৯০৫-৪৭ - চৌধুরী, সিরাজুল ইসলাম, ১৯৩৬- (ঢাকা : সংহতি, 2016)
Articles chiefly on the history of nationalism in Bengal since 1905-1947; includes articles on communalism.
গ্রন্থপঞ্জিগত নির্দেশিকা ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan, Development Book Agency
In Bengali; includes passages in English.
Keywords: Nationalism -- India -- Bengal -- 20th century -- History; Communalism -- India -- Bengal -- 20th century; Bengal (India) -- History -- 20th century